Developing transferrable skills through entrepreneurship projects: Student’s experiences and challenges - Fernandes, Sandra (2017)
This paper aims to analyse the impact of the curricular unit “Entrepreneurship” on the development of student’s transversal skills. The study takes place in a curricular unit that is transversal to all third year bachelor programs of the Portucalense University, located in the north of Portugal. “Entrepreneurship” is part of the study plan of programs such as Psychology, Social Education, Tourism, Economics, Law, Management, Informatics, Management and Information Systems and Hospitality Management. In this curricular unit, students are challenged to develop an entrepreneurial project based on a business idea that must be explored and improved throughout the semester. In this paper, results from an ongoing study based on the development of a questionnaire, designated "Evaluation of Psychopedagogical Practices of the Entrepreneurship Project – QAPPPE”. The questionnaire was applied, at the end of the semester, to all students participating in the Entrepreneurship course unit, in the academic year of 2016/2017. Issues concerning student satisfaction with the project, developed skills, teamwork, teacher´s role, student assessment and the overall evaluation of the project are explored in the paper.